PEMBERDAYAAN MASYARAKAT BERBASIS SUMBER DAYA LOKAL MELALUI PRODUK OLAHAN TERONG DI DESA SIDO JANGKUNG) [LOCAL RESOURCES BASED COMMUNITY EMPOWERMENT (THROUGH THE EGGPLANT PROCESSED PRODUCTS IN SIDO JANGKUNG VILLAGE)] - Sri Juni Woro Astuti; Supriyanto -; Sujani - (Jurnal Sinergitas PKM & CSR, 2019)
Indonesia as an agricultural country certainly has abundant natural resources. One of the natural resources in the agricultural sector is various types of food crop varieties, including vegetables and fruits that have great potential for increased utilization. Eggplant is one of the vegetables that contains a lot of anti-oxidants and is easy to cultivate. Likewise in Menganti District, Gresik regency, East Java, the potential of the eggplant is very abundant especially in Sidojankung Village. From this potential resource, women's groups in Sido Jangkung village took the initiative to increase the economic value of eggplant into various kinds of processed beverage products and foods such as juice and eggplant ice cream, bread and eggplant dodol. However, so far these creative businesses can not develop as expected. Problems faced include the production and management problems. In terms of production problems, food and beverage products need to be improved to be more durable. It is also still a lack of adequate equipment and packaging are less attractive. Whereas the problems of the management aspect is the lack of promotion or marketing capabilities, as well as yet to implement financial management for small businesses. Based on the problems faced above, this community service activity aims to empower communities by helping partner group consisting of women in the Sido Jangkung village in order to improve the product quality and marketing so that it can become an alternative income of their household. The method applied to achieve this goal is to provide training in production and management and provide equipment assistance.